Antioxidants in Foods - Seiquer, Isabel; Palma, José (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Antioxidants in food have a dual role; on the one hand, they preserve the quality and shelf life of food products; on the other hand, they function as an external aid, helping to defend our living cells from the threat of oxidative stress. Therefore, foods rich in antioxidants are a useful tool to reduce morbidity and prevent degenerative diseases. Consequently, research related to antioxidants is continually growing. This book brings together 21 articles regarding the latest advances in the most relevant fields of food antioxidant research; from the identification and characterization of new active components, to their molecular mechanisms and the scientific evidence of their clinical use and effectiveness.